2018
DOI: 10.1159/000495869
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Preconditioning of Human MSCs: a Direct Evidence of HIF-1α and Collagen Type XV Correlation

Abstract: Background/Aims: Mesenchymal stromal cells (MSCs) hold considerable promise in bone tissue engineering, but their poor survival and potency when in vivo implanted limits their therapeutic potential. For this reason, the study on culture conditions and cellular signals that can influence the potential therapeutic outcomes of MSCs have received considerable attention in recent years. Cell maintenance under hypoxic conditions, in particular for a short period, is beneficial for MSCs, as low O2 tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…The ability of hOBs to migrate to the wounded area was assessed using the scratch assay method [ 21 ]. Cells were seeded into 24-well plates and incubated with complete medium at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The ability of hOBs to migrate to the wounded area was assessed using the scratch assay method [ 21 ]. Cells were seeded into 24-well plates and incubated with complete medium at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, MSCs are routinely cultured under 21% oxygen pressure conditions that several times exceeds the physiological level available in their natural niches (which ranges from 1% to 7% O 2 ) [6][7][8]. There are several reports confirming the beneficial effect of hypoxia and hypoxic preconditioning on migration, regenerative potential, proangiogenic activity and expanded survival of MSCs [9][10][11][12][13][14]. However, culturing cells under low oxygen conditions is demanding, has some limitations and multiplies the costs of MSCs culture.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand their function in the local environment, it is necessary to evaluate whether MSC also tolerate lower oxygen concentrations (<2%) . In fact, it has been demonstrated that hypoxic conditions (1% O 2 ) affect MSC function by reducing their senescence, increasing proliferation, and maintaining the differentiation properties . In addition, a hypoxic environment increases the expression of chemokine receptors such as CXCR4 and CXCR7 …”
mentioning
confidence: 99%